The effect of calcium phosphate nanoparticles on hormone production and apoptosis in human granulosa cells - Gao Li; Chen Zhen; Li Hao; Chen Liang; Cui Yugui; Qin Dingxia; Liu Xiaohui; Li Ying; Liu Jiayin (BMC, 2010)
Abstract Objectives Although many nanomaterials are being used in academia, industry and daily life, there is little understanding about the effects of nanoparticles on the reproductive health of vertebral animals, including human beings. An experimental study was therefore performed here to explore the effect of calcium phosphate nanoparticles on both steroid hormone production and apoptosis in human ovarian granulosa cells. Methods Calcium phosphate nanoparticles uptaking was evaluated by transmission electron microscopy (TEM). The cell cycle was assessed with propidium iodide-stained cells (distribution of cells in G0/G1, S, and G2/M phases) by flow cytometry. The pattern of cell death (necrosis and apoptosis) was analyzed by flow cytometry with annexin V-FITC/PI staining. The expression of mRNAs encoding P450scc, P450arom and StAR were determined by RT-PCR. Progesterone and estradiol levels were measured by radioimmunoassay. Results TEM results confirmed that calcium phosphate nanoparticles could enter into granulosa cells, and distributed in the membranate compartments, including lysosome and mitochondria and intracellular vesicles. The increased percentage of cells in S phase when cultured with nanoparticles indicated that there was an arrest at the checkpoint from phase S-to-G2/M (from 6.28 +/- 1.55% to 11.18 +/- 1.73%, p < 0.05). The increased ratio of S/(G2/M) implied the inhibition of DNA synthesis and/or impairment in the transition of the S progression stage. The apoptosis rate of normal granulosa cells was 7.83 +/- 2.67%, the apoptotic rate increased to 16.53 +/- 5.56% (P < 0.05) after the cells were treated with 100 microM calcium phosphate nanoparticles for 48 hours. Treatment with calcium phosphate nanoparticles at concentrations of 10-100 microM didn't significantly change either the progesterone or estradiol levels in culture fluid, and the expression levels of mRNAs encoding P450scc, P450arom and StAR after 48 h and 72 h period of treatment. Conclusion Calcium phosphate nanoparticles interfered with cell cycle of cultured human ovarian granulosa cells thus increasing cell apoptosis. This pilot study suggested that effects of nanoparticles on ovarian function should be extensively investigated.